Perspectives on effective coaching by those who have been coached. (30th March 2017) - Carter, Alison; Blackman, Anna; Hicks, Ben; Williams, Matthew; Hay, Rachel
Abstract : Studies on coaching have largely explored effectiveness from the perspective of a coach or employing organization rather than that of the employee or coachee. There has also been a focus on 'successful' coaching, but little is known about unsuccessful coaching or the hindrances to achieving coaching success. Many empirical studies on training interventions have found that support and help for employees from managers and others within the workplace enhances training effectiveness and there is an assumption in coaching studies that this will also be true for coaching interventions. This study addresses the gap in academic literature by exploring survey responses from 296 industry professionals in 34 countries who had been, or were currently being, coached. The study found that facing barriers during the period of coaching engagements was common and we present a categorization framework of six barrier categories. Our analysis suggests that three of these barrier categories may be predictive of coachee perceptions of limited coaching effectiveness: difficulties with a coach; coaching relationships and overall coaching experience. The study also provides empirical evidence that suggests a lack of support from within an employing organization is not predictive of limited coaching effectiveness.